The Competent Teacher of a Gifted Pupil in Early Primary School Education - Expectations versus Reality. The Author's Own Study - Aneta Kamińska (Ignatianum University Press, 2020)
The aim of the article is to present the results of the study on early primary school teacher's preparation for working with gifted pupils. The study was conducted among 697 primary school teachers teaching in grades I, II, and III in Cracow and nearby towns. The theoretical aim of the article is to demonstrate, on the basis of the subject literature, the most important predispositions these teachers should possess. The author's own study has revealed that teachers are not adequately prepared to provide effective and engaging education for gifted pupils at an early school age. In the last part of the article the author indicates solutions aimed at improving this situation, e.g. enriching the offer of university study programmes for teachers in the area of education of gifted students; creating a position of a "teacher of gifted students"; creating separate centres supporting educational development of gifted students; and extending cooperation between all educational units.